Transient Performance of Radiator on Engine Rpm Variation with AC Loading - Made Ricki Murti (Department of Mechanical Engineering, University of Udayana, 2009)
Radiator is one of heat exchanger applications that has a function to remove out of heat must be able to operate properly for allowed engine temperature limit. Vehicles that operate on the street usually driving with varying rpm so that the heat produced by the combustion process is not constant and then this study analyze the performance of radiators as a function of time (transient condition). Tests is done on the condition of operating the engine with five rpm variations, each for one hour with air conditioning load and without air-conditioning load. The data to be collected includ the inlet and outlet temperature of radiator and radiator fluid volume flow. The results obtained is heat exhausted rate as a performance radiator is increasing as with increasing of engine rpm and at load conditions with the AC produces heat exhausted rate is greater than AC without AC load. The heat exhausted rate in an hour of machine operation still shows the system operates at a transient condition due to there still exists a numerical increase in the heat exhausted rate as a function of time.